Analysis of an Exegetic Tradition in the Mekhilta de-Rabbi Ishmael: The Meaning of 'Amanah in the Second and Third Centuries - Cohen, Norman J. (AJS review, 1984)
In the past few years, a number of works have appeared which have tried to utilize different methods in the analysis of midrashic and aggadic texts. These recent efforts include the application of literary structural analysis, formula comparison, linguistic tools, and form and redaction criticism, in addition to concern for the sitz im leben of particular passages, i.e., sociohistorical studies.